2017
DOI: 10.1002/cbf.3280
|View full text |Cite
|
Sign up to set email alerts
|

RGS3 inhibits TGF‐β1/Smad signalling in adventitial fibroblasts

Abstract: Recent evidence suggests that adventitial fibroblasts (AFs) are crucially implicated in atherosclerosis. However, the mechanisms by which AFs are dysfunctional and contribute to atherosclerosis remain unclear. This study aimed to investigate the role of regulator of G-protein signalling 3 (RGS3) in the regulation of AFs using apoE knockout mouse as the model. Pathological changes in aortic arteries of apoE knockout mice fed with hyperlipid diet were examined by Movat staining. The expression of RGS3, α-SMA, TG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…Furthermore, APOB is positively correlated with secreted protein acidic and rich in cysteine (SPARC) [ 71 ], which expression is frequently associated with the excessive deposition of collagen [ 72 ] and in BC, SPARC could promote TGF-β-induced epithelial-mesenchymal transition (EMT), and further promote the tumor metastasis [ 73 ]. The overexpression of HIF1A and TGFB1 were observed in APOE knockout mice [ 74 , 75 ]. In addition, NOTCH1 signaling drives metastasis through TGF-β-dependent neutrophil recruitment [ 76 ] and crosstalk between NOTCH1 and HIF-1α has been implicated in metastasis development [ 77 ].…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, APOB is positively correlated with secreted protein acidic and rich in cysteine (SPARC) [ 71 ], which expression is frequently associated with the excessive deposition of collagen [ 72 ] and in BC, SPARC could promote TGF-β-induced epithelial-mesenchymal transition (EMT), and further promote the tumor metastasis [ 73 ]. The overexpression of HIF1A and TGFB1 were observed in APOE knockout mice [ 74 , 75 ]. In addition, NOTCH1 signaling drives metastasis through TGF-β-dependent neutrophil recruitment [ 76 ] and crosstalk between NOTCH1 and HIF-1α has been implicated in metastasis development [ 77 ].…”
Section: Resultsmentioning
confidence: 99%
“…The overexpressed RGS3 in the tissues of patients with gastric cancer could lead to a poor prognosis, which could be negatively regulated by miR-126 (Wang et al, 2017). In addition, the abnormal expression of RGS3 might regulate the TGF-β signaling pathway by interfering with the heteromerization of Smad protein (Xu et al, 2017). Lu S et al reported that the overexpression of HOXD-AS1 in human hepatocyte tumors negatively regulated the expression level of RGS3, thereby inhibiting Dox-induced apoptosis (Lu S. et al, 2017), while overexpression of RGS3 in glioma cells promotes cell adhesion and metastasis (Tatenhorst et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Based on the functional property of UBE2S, it is possible that autoAbs to this protein may affect cellular response to DNA damage by interfering with ubiquitin modification at DNA damage sites [37]. In addition, RGS3, a G-protein signaling inhibitor, has been implicated in cell proliferation and apoptosis in cancer [40]. Whether antibodies to this antigen also impact other immune functions or renal disease regulated by G-proteins remains to be elucidated [41], [42].…”
Section: Discussionmentioning
confidence: 99%